Who Cares for the Family Caregivers of the Elderly during COVID-19 in Low-Middle Income Countries? A Commentary - Oyegbile, Yemisi Okikiade; Sibiya, Maureen Nokuthula (African Journal of Inter/Multidisciplinary Studies, 2022)
The considerable increase in the intensity and duration of care provided to the elderly by family caregivers warrants a detailed review of the support interventions available to these “invisible” individuals during the COVID-19 pandemic. Family caregivers had limited access to respite care due to the restrictions imposed by the COVID-19 protocols. This increased their stress and the burden of caregiving. This commentary article details the experiences of family caregivers of the elderly and establish the type of support interventions available to them during the pandemic, especially in low-and-middle-income countries. Random search of literature was conducted, and themes identified include: “fear of contagion”, “limited resources”, “knowledge deficit” and “grieving in solitary”. In addition, this article recommends strategies to mitigate the burden and stress experienced by them.